Rigour in Qualitative Studies: Are we on track? - Ani Wilujeng Suryani; Helianti Utami (Institute of Research and Community Outreach - Petra Christian University, 2020)
Prior research has explored qualitative studies in relation to the paradigms used. This paper enriches the literature by investigating the quality of qualitative studies in relation to the data collection method and participants' selection. In this study, we collected SNA qualitative paper proceedings from 2007 to 2017. Guided by the minimum criteria of the data collection method described in the literature review sections, we analyze those proceedings. We found the three most common methods used in the studies: interview, observation, and documentation. The majority of the paper clearly stated their data collection method. However, only a minority of them provides a clear description of how the data were collected and how to obtain participants/data used in their studies and why invite dthem in the research. Thus, it is suggested that researchers provide a detail explanation of their methods to show the rigour of the study that they conducted